Phytochemical Study of Some Medicinal Plants - Sarraf, S.; Ojha, A.C.; Rawat, G.S. (Asian Journal of Chemistry, 2010)
Adhatoda vasica Nees, Argemone mexicana Linn and Asparagus racemosus Willd and their parts have been analysed for protein and amino acids. In all, seventeen amino acids were identified in the various medicinal plants.